When Is Honesty the Best Policy? The Effect of Stated Company Intent on Consumer Skepticism - Foreh, Mark R.; Grier, Sonya (Journal of Consumer Psychology, 2003)
Prior research suggests that consumers evaluate firms more negatively if they attribute the firm's business practices to firm‐serving motivations rather than to motivations that serve the public good. We propose an alternative hypothesis: Firm‐serving attributions lower evaluation of the firm only when they are inconsistent with the firm's expressed motive. As such, the negative effect of consumer skepticism regarding a firm's motives can be inhibited by public acknowledgment of the strategic benefits to the firm. The power of this inhibition procedure was demonstrated in an experiment in which we manipulated the salience of firm‐serving benefits and the firm's publicly stated motive. Consumer evaluation of the sponsoring firm was lowest in conditions when firm‐serving benefits were salient and the firm outwardly stated purely public‐serving motives. This experiment also revealed that the potential negative effects of skepticism were the most pronounced when individuals engaged in causal attribution prior to company evaluation. Finally, in this study we measured the different effects on attribution and evaluation of 2 distinct forms of skepticism: situational skepticism, which is a momentary state of distrust of an actor's motivations, and dispositional skepticism, which is an individual's ongoing tendency to be suspicious of other people's motives.